2020
DOI: 10.3892/or.2020.7889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of claudin 1 on cell proliferation, migration and apoptosis in human cervical squamous cell carcinoma

Abstract: Claudin 1 is a member of the claudin protein family that serves an important role in tight junctions. Increased or decreased expression levels of claudin 1 are found in several diseases, including breast cancer and viral infections. However, the function of claudin 1 in cervical cancer remains controversial. The aim of the present study was to investigate the biological functions of claudin 1 in different human cervical cancer cell lines. First, SiHa and ME-180 cells with stable claudin 1 overexpression or kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…CLDNs have been implicated in cell proliferation and tumor progression [ 79 , 80 ]. Tongue squamous cell carcinoma, Cal27 cells, contain one of the simplest TJs, composed of CLDN1, JAM-A, and OCLN, thus presenting a good model for the study of proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…CLDNs have been implicated in cell proliferation and tumor progression [ 79 , 80 ]. Tongue squamous cell carcinoma, Cal27 cells, contain one of the simplest TJs, composed of CLDN1, JAM-A, and OCLN, thus presenting a good model for the study of proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the inhibition of ASF1B induces cell cycle arrest in cervical cancer cells ( 43 ). Shen et al ( 45 ) demonstrated that claudin 1 induces cell cycle arrest in cervical squamous cell carcinoma. In the present study, it was revealed that MCM2 expression was upregulated in cervical cancer tissues and cell lines and that silencing MCM2 induced cell cycle arrest at the G 0 /G 1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…All animal procedures were ratified by the Animal Ethics Committee of Affiliated Cancer Hospital of Zhengzhou University (Approval No. 2020–031-001) and performed according to the Guide for the Care and Use of Laboratory Animals (NIH, Bethesda, MD, USA) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%